Triple burden of malnutrition among Malaysian children aged 6 months to 12 years: current findings from SEANUTS II Malaysia - Bee Koon Poh; Jyh Eiin Wong; Shoo Thien Lee; Jasmine Siew Min Chia; Giin Shang Yeo; Razinah Sharif; Nik Shanita Safii; Nor Aini Jamil; Caryn Mei Hsien Chan; Nor MF Farah; Mohd Jamil Sameeha; Denise Koh; et al. (Public Health Nutrition, 2024)
Abstract